2017
DOI: 10.4103/ijpc.ijpc_153_16
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations to support nurses and improve the delivery of oncology and palliative care in India

Abstract: Context:Nurses in India often practice in resource-constrained settings and care for cancer patients with high symptom burden yet receive little oncology or palliative care training.Aim:The aim of this study is to explore challenges encountered by nurses in India and offer recommendations to improve the delivery of oncology and palliative care.Methods:Qualitative ethnography.Setting:The study was conducted at a government cancer hospital in urban South India.Sample:Thirty-seven oncology/palliative care nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…There has been a strong focus on standards of accountability for health care in LMIC, but historically, a lack of prioritization, or even neglect, of protective measures for nurses and others has been evident. We must promote standards, identify incentives, and provide a solid rationale to institutions and governments to prioritize access to PPE for all those handling hazardous drugs, and, in parallel, advance specialized nursing roles and education to develop proficiency in pediatric oncology nursing care and optimize patient outcomes …”
Section: Ethical Argumentation For Moral Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a strong focus on standards of accountability for health care in LMIC, but historically, a lack of prioritization, or even neglect, of protective measures for nurses and others has been evident. We must promote standards, identify incentives, and provide a solid rationale to institutions and governments to prioritize access to PPE for all those handling hazardous drugs, and, in parallel, advance specialized nursing roles and education to develop proficiency in pediatric oncology nursing care and optimize patient outcomes …”
Section: Ethical Argumentation For Moral Actionmentioning
confidence: 99%
“…We must promote standards, identify incentives, and provide a solid rationale to institutions and governments to prioritize access to PPE for all those handling hazardous drugs, and, in parallel, advance specialized nursing roles and education to develop proficiency in pediatric oncology nursing care and optimize patient outcomes. 42…”
Section: Protect From Harmmentioning
confidence: 99%
“…Several other guidelines and authors have suggested particular subjects for education and training for health care personnel in palliative care. Examples 7 , 28 , 29 include providing education in assessing and managing patients’ pain and other symptoms, recognition of metastases, communication skills, leadership skills, cultural communication, 28 and basic oncology skills ( Table 3 for training resources from Maximal settings). 29 …”
Section: Recommendationsmentioning
confidence: 99%
“…The WHO Palliative Care Strategy states that policymakers should address “medicine availability, education, and government policy”; WHO also provides a model on access to opioids. According to LeBaron et al, 29 hospitals should have a first priority of making oral IR morphine available. “Institutions that have been successful in procuring morphine…could serve as role models and mentors to other institutions who wish to improve access to pain relief for their patients.…”
Section: Recommendationsmentioning
confidence: 99%
“…[ 1 ] Even more important is sensitizing the young medical and nursing graduates to the basics of palliative care. [ 47 ] Ongoing communication with the regulatory bodies like the Medical Council of India(MCI) is in progress. [ 1 ]…”
Section: Iversity In H Ealth-care mentioning
confidence: 99%